Patient radiation dose in percutaneous biliary interventions: recommendations for DRLs on the basis of a multicentre study - Schmitz, Daniel; Vogl, Thomas; Nour-Eldin, Nour-Eldin Abdelrehim; Radeleff, Boris; Kröger, Jens-Christian; Mahnken, Andreas H.; Ittrich, Harald; Gehl, Hans-Björn; Plessow, Bernd; Böttcher, Joachim; Tacke, Josef; Wispler, Markus; et al. (European radiology, 2019)
ObjectivePercutaneous biliary interventions (PBIs) can be associated with a high patient radiation dose, which can be reduced when national diagnostic reference levels (DRLs) are kept in mind. The aim of this multicentre study was to investigate patient radiation exposure in different percutaneous biliary interventions, in order to recommend national DRLs.MethodsA questionnaire asking for the dose area product (DAP) and the fluoroscopy time (FT) in different PBIs with ultrasound- or fluoroscopy-guided bile duct punctures was sent to 200 advanced care hospitals. Recommended national DRLs are set at the 75th percentile of all DAPs.ResultsTwenty-three facilities (9 interventional radiology depts. and 14 gastroenterology depts.) returned the questionnaire (12%). Five hundred sixty-five PBIs with 19 different interventions were included in the analysis. DAPs (range 4-21,510 cGy·cm2) and FTs (range 0.07-180.33 min) varied substantially depending on the centre and type of PBI. The DAPs of initial PBIs were significantly (p < 0.0001) higher (median 2162 cGy·cm2) than those of follow-up PBIs (median 464 cGy·cm2). There was no significant difference between initial PBIs with ultrasound-guided bile duct puncture (2162 cGy·cm2) and initial PBIs with fluoroscopy-guided bile duct puncture (2132 cGy·cm2) (p = 0.85). FT varied substantially (0.07-180.33 min).ConclusionsDAPs and FTs in percutaneous biliary interventions showed substantial variations depending on the centre and the type of PBI. PBI with US-guided bile duct puncture did not reduce DAP, when compared to PBI with fluoroscopy-guided bile duct puncture. National DRLs of 4300 cGy·cm2 for initial PBIs and 1400 cGy·cm2 for follow-up PBIs are recommended.Key Points• DAPs and FTs in percutaneous biliary interventions showed substantial variations depending on the centre and the type of PBI.• PBI with US-guided bile duct puncture did not reduce DAP when compared to PBI with fluoroscopy-guided bile duct puncture.• DRLs of 4300 cGy·cm2for initial PBIs (establishing a transhepatic tract) and 1400 cGy·cm2for follow-up PBIs (transhepatic tract already established) are recommended.